Ensnarement during imprisonment: re‐conceptualizing theoretically driven policies to address the association between within‐prison sanctioning and recidivism - Silver, Ian A. (Criminology & public policy, 2018)
We used data collected during the Evaluation of Ohio's Prison Programs. The analytical sample of N = 63,772 inmates represents one of the largest samples used to assess the association between within‐prison sanctioning and recidivism. Latent class growth analysis (LCGA) demonstrated that five guilty sanctioning clusters existed within the data: Persistent (0.72%), Very High Decline (0.11%), High Decline (1.38%), Moderate Decline (27.03%), and Abstainers (70.75%). The examination of sanctioning cluster classification on post‐release recidivism suggested that greater exposure to formal sanctions during imprisonment predicted recidivism 1, 2, and 3 years post‐release.